146k views
2 votes
(6×10^2) ÷ (3×10^-3)

2 Answers

6 votes

Hi!

Lets go through this together.

Using the operation, PEMDAS, we start from left, then go to right.

since there are two pairs of parenthesis, we start with the one on the left.

(6x10^2)

so now, we do the exponent, 10^2

10x10= 100

So our answer for this part is 100.

Now we have (6x100)

6x100=600

So now, the equation is 600÷(3x10^-3)

Now, we do the parenthesis on the right.

(3x10^-3)

First, we do the exponent, 10^-3

10x-10x-10= 1,000

so now, the equation is (3x1,000)

Now, we multiply.

3x1,000=3,000

So now, the equation is 600 ÷ 3,000

600 ÷ 3,000 = 0.2

So, your answer is 0.2.

__________________________________________________________

(6 x 10^2) ÷ (3 x 10^-3)

=(6 x 100) ÷ (3 x 10^-3)

= 600 ÷ (3 x 10^-3)

= 600 ÷ (3 x 1,000)

= 600 ÷ 3,000

= 0.2

(also, the scientific notation is 2x10^2)

__________________________________________________________

Hope this helps!

Let me know if you need anymore help!

Yours truly,

~~~PicklePoppers~~~

User Shavareppa
by
4.8k points
3 votes

Answer:

2*10²

Reduce the expression, if possible, by cancelling the common factors.

Scientific Notation:

User Jorge Balleza
by
5.6k points